Component Characterization, In Vitro Activities and Molecular Mechanism of Cydonia oblonga Mill. against Diabetic - Bingqing Chi; Xilong Liang; Lihua Wang; Yifei Bian; Meng Zhang; Zhixin Tang; Danyang Wang; Zhenhua Tian (MDPI AG, 2022)
Cydonia Oblonga Mill. is widely distributed in Turkey, Uzbekistan and China and commonly used by the food industry to produce jam, jelly and candies. The aim of this study was to investigate the in vitro antidiabetic activity and anti-diabetic mechanism of Cydonia Oblonga Mill. fruit (COMF). The chemical compositions were further characterized in COMF by UPLC-Q-Orbitrap/MS and 65 components including 22 flavonoids, 16 organic acids, 11 polyphenols, 5 amino acids, 3 pentacyclic triterpenoids and 8 other compounds were identified. The antioxidant activity by DPPH scavenging method and α-glucosidase inhibitory activity were tested. Furthermore, we detected the effects of COMF extract on the proliferation activity of HUVECs, cell viability of HUVECs under H2O2-induced oxidative stress, and NO production. Then, molecular docking activity and α-glucosidase inhibitory activity of seven key flavonoid components selected by bioinformatics analysis and literature in the COMF were studied. Among them, quercetin showed potent inhibitory activity, kaempferol, isorhamnetin, luteolin and apigenin demonstrated moderate inhibitory activity, while rutin and epicatechin exhibited poor inhibitory activity. Subsequently, the effects of quercetin, kaempferol, isorhamnetin, leteolin and apigenin on the gene expression levels of AKT1, IL-6 and VEGFA were verified by real-time fluorescence quantification (RT-qPCR). Molecular biology result showed that different active ingredients can significantly recover the levels of AKT1, IL-6 and VEGFA in HUVECs injured by high glucose.